2010
DOI: 10.4103/0377-4929.68292
|View full text |Cite
|
Sign up to set email alerts
|

Geographical location and age affects the incidence of parasitic infestations in school children

Abstract: One of the greatest challenges for healthcare professionals is the prevention and treatment of protozoal and helminthic parasitic infections. From our study we conclude that the prevalence of different pathogenic species of amoeba such as Entamoeba histolytica (4.2 vs. 0%) and G. lamblia (17.9 vs. 14%), (P value was equal to 1) was significantly higher among rural children compared to children from urban areas. In contrast, the prevalence of nematodes such as A. lumbricoides (21% vs. 1.1%), T. trichiura (8% vs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
18
1
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 4 publications
6
18
1
4
Order By: Relevance
“…The distribution of Blastocystis subtypes is geographically different 14 ; many studies have shown that subtype 3 was most frequently observed among humans. 2,32 In Thailand, subtype 1 was the most dominant subtype, followed by subtype 2 in school children of a rural community in the central of Thailand.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The distribution of Blastocystis subtypes is geographically different 14 ; many studies have shown that subtype 3 was most frequently observed among humans. 2,32 In Thailand, subtype 1 was the most dominant subtype, followed by subtype 2 in school children of a rural community in the central of Thailand.…”
Section: Discussionmentioning
confidence: 99%
“…in Thai children ranged from 4.5% to 18.9%, during 2006-2010. 2,5,13 The variations of the prevalence of parasitic infection including Blastocystis infection might depend on the study population or geographic location, age, 14 and detection methods. 15,16 Using PCR technique, the highest prevalence of Blastocystis infection was found among children of Senegal River Basin, which was 100%.…”
Section: Discussionmentioning
confidence: 99%
“…However, this rate was lower than the rate reported in Damghan and Bam [28,29] but significantly higher than that in Illam and Yazd [24,30]. Such differences in the prevalence of different parasitic diseases could be associated with environmental, or socio -economic factors such as, the rate of humidity, temperature and dust, lack of health facilities in families or in day care centers; unhealthy handling of sewages; the residence place(rural or urban) and also the time of the study [22,29,31].…”
Section: Discussionmentioning
confidence: 99%
“…Fatores ambientais como a condição climática, tipo de solo, saneamento, juntamente com os hábitos culturais e de higiene das populações são fatores frequentemente associados à exposição e colonização por parasitas intestinais 2 . Na Região Amazônica, essa situação constitui um dos principais problemas de saúde pública, especialmente em comunidades ribeirinhas onde as condições de saneamento básico são precárias, inexistindo infraestrutura que viabilize o destino adequado dos dejetos, bem como o acesso à água potável 3,4,5 . Desse modo, o uso da água do rio nas atividades domésticas e higiene pessoal representam um risco à saúde da população devido à presença de diferentes patógenos que são veiculados pela água contaminada.…”
Section: Introductionunclassified